Management of Esophageal Foreign Body Using Endoscopic Approach: an Experience from Kathmandu Medical College Teaching Hospital - Shrestha, Diva (Journal of Kathmandu Medical College, 2018)
Background: Esophageal foreign body is a common otolaryngological emergency encountered in clinical practice. The cases with esophageal foreign body need prompt medical attention and appropriate endoscopic or surgical intervention. The type of foreign body varies in different age groups and the level of impaction also varies accordingly. The foreign body in upper esophagus can be removed with safer and easier non-surgical techniques. Objectives: The objective of this study was to determine the demography, management approach and outcome of esophageal foreign body cases presented to Kathmandu Medical College Teaching Hospital. Methodology: This is a prospective study conducted in Kathmandu Medical College Teaching Hospital. The data was collected from the medical records of cases that presented to Kathmandu Medical College Teaching Hospital with clinical diagnosis of esophageal foreign body from July 2013 to July 2017. Results: Out of 101 cases of esophageal foreign body, there were 57% cases of chicken bone, followed by 17% mutton bone and 12% meat bolus. Among all, 71% cases had endoscopic removal of foreign body within six hours of presentation and 29% had endoscopic removal of foreign body between six to twelve hours. The most common age group was fifth decade of life. One patient had post-operative mediastinitis. Conclusion: The endoscopic approach is the mainstay of management in foreign body esophagus and timely management leads to successful outcome. Journal of Kathmandu Medical College, Vol. 6, No. 4, Issue 22, Oct.-Dec., 2017, Page: 136-139